Evaluación de proyectos de sistemas eléctricos de uso final en edificios educativos. Caso de estudio (2022)
This research proposes the development of a procedure for evaluating end-use electrical system projects in educational buildings that allow safety, reliability, minimum losses, and access to various energy measurement points. Initially, the electrical design criteria for buildings that meet the parameters of safety, reliability, minimum losses, and access to various energy measurement points are analyzed, considering components and topologies following the regulatory requirements in Colombia. Subsequently, the steps that allow the evaluation of electrical system projects in educational buildings are described in sequence, explaining each tool used in the procedure. Finally, the procedure is evaluated from a case study in an educational building with various operating scenarios considering different technologies and modes of operation.